2018
DOI: 10.1080/02763869.2018.1404389
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Outreach: Curriculum Development and Skills Training to Health and Information Professionals

Abstract: With funding from the National Library of Medicine HIV/AIDS Community Information Outreach Program (ACIOP), librarians at the University of Florida Health Sciences Libraries partnered with university and community groups to facilitate collaboration, develop new information resources, develop information-seeking skills, and raise general awareness surrounding HIV/AIDS risks, prevention, and treatment. This article describes the skills development elements of the project, including development and implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Meanwhile, with funding from the NLM, a group of librarians at the University of Florida Health Sciences Libraries have partnered with community groups and university affiliates to develop a curriculum for health and social service providers on finding relevant literature about HIV and AIDS [ 12 ]. Because these resources are free for other librarians to modify and reuse as learning tools within their institutions and communities, the librarian involved with the HIV ECHO has been taking advantage of these resources to better prepare ECHO participants to care for their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, with funding from the NLM, a group of librarians at the University of Florida Health Sciences Libraries have partnered with community groups and university affiliates to develop a curriculum for health and social service providers on finding relevant literature about HIV and AIDS [ 12 ]. Because these resources are free for other librarians to modify and reuse as learning tools within their institutions and communities, the librarian involved with the HIV ECHO has been taking advantage of these resources to better prepare ECHO participants to care for their patients.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance access to high-quality HIV/AIDS resources for this population, we utilized two new techniques: graphic novels and social media marketing. Graphic novels or comics (used synonymously in this project) are an effective tool for health information education, and graphic medicine is a growing area of work [5]. In a 1994 study, Wells found that comics are the easiest format for disseminating HIV/AIDS information, particularly to individuals with low literacy [6].…”
Section: Introductionmentioning
confidence: 99%